2022
DOI: 10.5847/wjem.j.1920-8642.2022.060
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the precision of the pSOFA and SIRS scores in predicting sepsis-related deaths among hospitalized children: a multi-center retrospective cohort study

Abstract: BACKGROUND:The latest sepsis definition includes both infection and organ failure, as evidenced by the sequential organ failure assessment (SOFA) score. However, the applicability of the pediatric SOFA score (pSOFA) is not yet determined. This study evaluated the effectiveness of both pSOFA and system inflammatory reaction syndrome (SIRS) scores in predicting sepsis-related pediatric deaths.METHODS: This is a retrospective multi-center cohort study including hospitalized patients <18 years old with diagnosed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…A multicenter binational cohort study of PICUs in Australia and New Zealand was conducted by Schlapbach et al (10), and compared the predictive efficacy of SIRS, age-adapted SOFA, rapid SOFA, and PEdiatric Logistic Organ Dysfunction-2 scores for outcomes in children with sepsis, and the results suggested that the SIRS criteria lacked specificity and failed to identify infected children at higher risk of death. Other researchers have reached the same conclusion (29, 30). It is well known that sepsis in children has a rapid progression and high early mortality.…”
Section: Discussionsupporting
confidence: 65%
“…A multicenter binational cohort study of PICUs in Australia and New Zealand was conducted by Schlapbach et al (10), and compared the predictive efficacy of SIRS, age-adapted SOFA, rapid SOFA, and PEdiatric Logistic Organ Dysfunction-2 scores for outcomes in children with sepsis, and the results suggested that the SIRS criteria lacked specificity and failed to identify infected children at higher risk of death. Other researchers have reached the same conclusion (29, 30). It is well known that sepsis in children has a rapid progression and high early mortality.…”
Section: Discussionsupporting
confidence: 65%
“…The sepsis scores could not be calculated for some patients because it requires tests which were not performed or documented; this is a limitation of its use in clinical practice especially in developing countries. 35 The same study found pSOFA to be a better predictor of death than SIRS score. 35 In our cohort, the pSOFA and SIRS score yielded different results in patients in which it could be calculated; the SIRS score suggested sepsis in most of the patients, but the pSOFA score was not suggestive of sepsis.…”
Section: Discussionmentioning
confidence: 92%
“… 35 The same study found pSOFA to be a better predictor of death than SIRS score. 35 In our cohort, the pSOFA and SIRS score yielded different results in patients in which it could be calculated; the SIRS score suggested sepsis in most of the patients, but the pSOFA score was not suggestive of sepsis. The invasiveness of the organism as shown by the CSF results also supports true infection.…”
Section: Discussionmentioning
confidence: 92%
“…Various predictive models and scoring systems for neonatal sepsis have been developed and applied in diagnostic settings and retrospective studies. [7][8][9]. The clinical perinatal risk assessment program and the development guidelines for EOS, such as the National Institute for Health and Care Excellence (NICE) sepsis guideline [10], and Centers for Disease Control and Prevention (CDC) and the American Academy of Pediatrics (AAP) guidelines for EOS risk assessment [11], play crucial roles in this regard.…”
Section: Screening and Diagnosismentioning
confidence: 99%